2002
DOI: 10.1038/sj.bjc.6600498
|View full text |Cite
|
Sign up to set email alerts
|

Space-time clustering analyses of childhood acute lymphoblastic leukaemia by immunophenotype

Abstract: Space-time clustering analyses of acute lymphoblastic leukaemia in children, by immunophenotype, were carried out using a population-based registry. Significant evidence was found of space-time clustering for cases of the precursor B-cell sub-type, in the childhood peak, based on time and location at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 10 publications
7
43
0
Order By: Relevance
“…This result is similar to our previous study [24]. Compared to studies in high income and low-income countries our finding is relatively high for T-lineage ALL [25][26][27][28][29][30][31][32][33][34][35]. Expression of CD10 and CD34 also varies in different studies ( Table 1).…”
Section: Discussionsupporting
confidence: 76%
“…This result is similar to our previous study [24]. Compared to studies in high income and low-income countries our finding is relatively high for T-lineage ALL [25][26][27][28][29][30][31][32][33][34][35]. Expression of CD10 and CD34 also varies in different studies ( Table 1).…”
Section: Discussionsupporting
confidence: 76%
“…A space -time interaction between dates and places of diagnoses of ALL has often been reported within small temporal and spatial distances (Glass et al, 1971;Draper, 1991;Gilman and Knox, 1991;Gilman et al, 1999;Birch et al, 2000;Akhtar et al, 2005), especially among young children (Glass et al, 1971;Gilman et al, 1999;Birch et al, 2000). Birch et al also evidenced a space -time interaction between the dates of diagnoses and the places of birth, while McNally et al (2002) found a significant interaction between both places and dates of birth for the precursor B-cell subtype of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies investigated both [20,21,22]. Four found no spatial clustering and clusters at all [8][9][10][11], four found statistically significant results for at least one subgroup [14,16,21,22], and five found spatial clustering for the overall group of leukemia [12,13,15,17,20]. The five studies which investigated space-time interaction all found statistically significant results [18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Ten had their focus on clusters [8,9,10] and spatial clustering [11,12,13,14,15,16,17], two on space-time interaction alone [18,19]. Three studies investigated both [20,21,22]. Four found no spatial clustering and clusters at all [8][9][10][11], four found statistically significant results for at least one subgroup [14,16,21,22], and five found spatial clustering for the overall group of leukemia [12,13,15,17,20].…”
Section: Introductionmentioning
confidence: 99%